Renal Biopsy Prognostic Findings in Children With Atypical Hemolytic Uremic Syndrome - GÖKCE, İBRAHİM (SAGE PUBLICATIONS INC, 2020)
Background The aim of this study was to investigate the histopathological findings in kidney biopsies in children with atypical hemolytic uremic syndrome (aHUS) and to determine whether specific pathological findings in aHUS have a prognostic value. Methods Renal biopsy specimens of 29 patients who were recorded in the national Turkish aHUS registry database were available for review. Histopathological findings were compared with the clinical and laboratory features at the presentation and the final outcome. Results The mean age at presentation and follow-up period was 4.9 +/- 3.9 and 3.9 +/- 3.0 years, respectively. The median time interval from the first symptom to biopsy was 10 days. Vascular thrombosis and interstitial fibrosis were significantly related to chronic kidney disease (CKD) requiring dialysis or kidney transplantation during follow-up (5.6-fold, for both). Glomerular necrosis, cortical necrosis, and glomerular sclerosis were markedly associated with CKD without dialysis (6.2-fold, 13.3-fold, and 8.8-fold, respectively). However, presence of endothelial swelling, subendothelial widening, and fragmented erythrocytes was found to be correlated with a favorable final outcome. Conclusions Presence of vascular thrombosis, cortical necrosis, and glomerular sclerosis in histopathological evaluation correlated with developing CKD. Chronic changes in the interstitial compartment were also related to poor prognosis, a finding that has been shown for the first time in pediatric aHUS cases.
Keywords: atypical hemolytic uremic syndrome; cortical necrosis; glomerular sclerosis; interstitial fibrosis; prognosis; thrombotic microangiopathy; tubular atrophy; APOPTOSIS; CELLS